2014
DOI: 10.3343/alm.2014.34.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Levels of Natural Anticoagulants in Disseminated Intravascular Coagulation: High Prognostic Value of Antithrombin and Protein C in Patients with Underlying Sepsis or Severe Infection

Abstract: BackgroundDysfunctional natural anticoagulant systems enhance intravascular fibrin for mation in disseminated intravascular coagulation (DIC), and plasma levels of natural anti coagulants can be used in the diagnosis and prognosis of DIC. Herein, the diagnostic value of 4 natural anticoagulants was assessed, and the prognostic value of antithrombin and protein C were validated in a large population.MethodsPart 1 study included 126 patients with clinically suspected DIC and estimated plasma levels of 4 candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…Thus, we think that AT is an excellent discriminator of the severity of sepsis. Recently, Choi et al [ 54 ] reported a significant correlation between AT and the DIC score in patients with sepsis, suggesting that AT is a good indicator of DIC severity. Indeed, AT had a significant prognostic power in a Kaplan-Meier analysis, showing a higher hazard ratio than conventional coagulation markers, such as D-dimer.…”
Section: Reviewmentioning
confidence: 99%
“…Thus, we think that AT is an excellent discriminator of the severity of sepsis. Recently, Choi et al [ 54 ] reported a significant correlation between AT and the DIC score in patients with sepsis, suggesting that AT is a good indicator of DIC severity. Indeed, AT had a significant prognostic power in a Kaplan-Meier analysis, showing a higher hazard ratio than conventional coagulation markers, such as D-dimer.…”
Section: Reviewmentioning
confidence: 99%
“…big-h3 (also known as TGF-bi) is a secreted protein found in the ECM and it has an N-terminal secretory signal (aa 1-23), four FAS1 homologous internal domains, and a cell attachment site (RGD) at its C terminus (4). big-h3 binds to the ECM through interaction of the YH motif in its FAS1 domains with collagens I, II, IV, and VI (5,6). Its FAS1 domain interacts with its a3b1, aVb3, and aVb5 integrins on the cell surface.…”
mentioning
confidence: 99%
“…While 40% activity of AT III is seen in full blown DIC. Choi et al 16 reported a correlation between AT and the DIC scores in septic patients. This suggests that AT level is a good indicator of DIC severity.…”
Section: Discussionmentioning
confidence: 96%